2012
DOI: 10.1111/j.1948-7134.2012.00195.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a peridomestic mosquito trap for integration into an Aedes aegypti (Diptera: Culicidae) push-pull control strategy

Abstract: We determined the feasibility of using the BG-Sentinel™ mosquito trap (BGS) as the pull component in a push-pull strategy to reduce indoor biting by Aedes aegypti. This included evaluating varying numbers of traps (1-4) and mosquito release numbers (10, 25, 50, 100, 150, 200, and 250) on recapture rates under screen house conditions. Based on these variations in trap and mosquito numbers, release intervals were rotated through a completely randomized design with environmental factors (temperature, relative hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…However, further investigations and larger scale Þeld studies are necessary to further evaluate the effect of BGS mass trapping. A pushÐpull strategy where BGS is the pull component and spatial repellents or contact irritant chemicals are the push component, as recently proposed (Paz-Soldan et al 2011, Salazar et al 2012, also seems to be a promising approach. For further cluster-randomized trials of BGS mass trapping, a higher number of clusters should be included and serological investigations should be performed during periods of high dengue transmission to be able to further investigate the cost effectiveness of the strategy and the effect of the traps on disease transmission.…”
Section: Discussionmentioning
confidence: 97%
“…However, further investigations and larger scale Þeld studies are necessary to further evaluate the effect of BGS mass trapping. A pushÐpull strategy where BGS is the pull component and spatial repellents or contact irritant chemicals are the push component, as recently proposed (Paz-Soldan et al 2011, Salazar et al 2012, also seems to be a promising approach. For further cluster-randomized trials of BGS mass trapping, a higher number of clusters should be included and serological investigations should be performed during periods of high dengue transmission to be able to further investigate the cost effectiveness of the strategy and the effect of the traps on disease transmission.…”
Section: Discussionmentioning
confidence: 97%
“…Detritus), they are more economical in spite of their relatively high maintenance costs, and they have a negligible impact on wildlife. Because they are located in human-inhabited areas, mosquito traps could provide a useful complementary tool for the control of container-inhabiting species such as Aedes albopictus and Aedes aegypti, which pose public health problems, and for which traditional integrated mosquito management approaches based on larvae control are inefficient [18,19,20]. Our experiment suggest that the observed 70% reduction in the mosquito nuisance could be increased by combining different olfactive lures, by optimizing the position of traps relative to environmental conditions, and by increasing trap numbers to improve the protecting belt effect.…”
Section: Discussionmentioning
confidence: 99%
“…The screen house measures 4 m (width) × 3.5 m (height) × 40 m (length) and is located on-site with the experimental huts [34]. The screen house is subdivided into four 10 m long cubicles using metal partitions, each with a space volume of 140 m 3 (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have confirmed that the BGS trap effectively removes Ae. aegypti from a controlled environment [34]. However, the effects of exposure to repellents, or sublethal doses of insecticides, on BGS trap collections have not been previously evaluated.…”
Section: Introductionmentioning
confidence: 99%